2004
DOI: 10.1021/es034856q
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Molecular Interactions of Oxytetracycline in Clay and Organic Matter:  Insights on Factors Affecting Its Mobility in Soil

Abstract: The interactions of oxytetracycline with model clay adsorbents were investigated as a function of suspension pH. The clay adsorbents used were native montmorillonite (SWy-2), Na-montmorillonite (Na-SWy-2), and hexadecyl trimethylammonium-montmorillonite (HDTMA-montmorillonite). The adsorption of oxytetracycline to the clay could be described by Freundlich-type adsorption isotherms. It was observed that the adsorption of oxytetracycline in the native and sodium forms of montmorillonite decreases with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
279
6
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(343 citation statements)
references
References 33 publications
33
279
6
12
Order By: Relevance
“…2). The rate of decrease was small in comparison with the reports of Doi and Stoskopf (2000) and Kulshrestha et al (2004), who showed that adsorption decreased rapidly over this pH range and reported a strong correlation between pH and the sorption capacity of TC. Adsorption increased slightly at pH 10.…”
Section: Effect Of Ph On Otc Sorption Onto Untreated Montmorillonitecontrasting
confidence: 66%
“…2). The rate of decrease was small in comparison with the reports of Doi and Stoskopf (2000) and Kulshrestha et al (2004), who showed that adsorption decreased rapidly over this pH range and reported a strong correlation between pH and the sorption capacity of TC. Adsorption increased slightly at pH 10.…”
Section: Effect Of Ph On Otc Sorption Onto Untreated Montmorillonitecontrasting
confidence: 66%
“…7). Thus, soil solution pH is an important factor influencing the bioavailability of OTC in soil (Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005) and the transport from soil to plant. Time-dependent uptake of OTC by alfalfa showed that there was an equilibrium status of OTC uptake after 4 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Denmark, concentrations of oxytetracycline ranging from 2.5 to 50 mg g À1 in soil and from 33 to 2000 mg g À1 in pig manure have been reported (Loke et al, 2002). The fate of antibiotics, including sorption and fixation, mobility and transport in soil, has been well documented (Tolls, 2001;Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005), whereas knowledge of their toxicity to plants and their uptake and transport into plants is poorly understood (Boxall et al, 2003;Thiele-Bruhn, 2003). The accumulation may or not affect the growth and development of plants; however, the uptake into plants may represent an important exposure pathway of these compounds to humans and other biota.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, residual concentrations of pharmaceutical antibiotics can be found in soils, surface and ground water (Hamscher et al, 2002;Kolpin et al, 2002;Simon, 2005). The fate of antibiotics including sorption and fixation, mobility and transport is well documented (Tolls, 2001;Figueroa et al, 2004;Kulshrestha et al, 2004), whereas the knowledge about their ecotoxicity and the effect of antibiotics on soil microbial functioning is scarce (Thiele-Bruhn, 2003;Boxall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%